Gregorio Rodríguez Herrera (ed.), Florilegios latinos y sociedad, Vigo, Academia del Hispanismo, 2020, - López-Muñoz, Manuel (Revista de Estudios Latinos, 2021)
Gregorio Rodríguez Herrera (ed.), Florilegios latinos y sociedad, Vigo, Academia del Hispanismo, 2020, 276 pp. ISBN 978-84-17696-33-7.